2020
DOI: 10.1093/hmg/ddaa169
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors of ME/CFS: a critical review

Abstract: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a complex multisystem illness that lacks effective therapy and a biomedical understanding of its causes. Despite a prevalence of approximately 0.2–0.4% and its high public health burden, and evidence that it has a heritable component, ME/CFS has not yet benefited from the advances in technology and analytical tools that have improved our understanding of many other complex diseases. Here we critically review existing evidence that genetic factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 61 publications
(63 reference statements)
0
46
0
Order By: Relevance
“…Two studies reported many candidate SNPs for such association, but none was located in ACE or ACE2 11 , 86 . Two other studies did not find any significant SNPs associated with ME/CFS 32 , 88 . The most optimistic study reported thousands of SNPs related to the disease [ 87 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Two studies reported many candidate SNPs for such association, but none was located in ACE or ACE2 11 , 86 . Two other studies did not find any significant SNPs associated with ME/CFS 32 , 88 . The most optimistic study reported thousands of SNPs related to the disease [ 87 ].…”
Section: Discussionmentioning
confidence: 83%
“…Finally, our original idea was to perform a meta-analysis of ACE/ACE2 data from published genome-wide association studies on ME/CFS 11 , 32 , 86 , 87 , 88 . However, we could not materialize this idea, because such studies did not make their data publicly available.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if correcting multiple testing is taken into account in the analysis, the most likely finding is the identification of relatively few disease associations, as demonstrated by Smith et al (2011). In the worst-case scenario, correcting for multiple testing in studies with sample sizes leads to the absence of evidence for any disease association, as reported by different studies (Dibble et al, 2020; Herrera et al, 2018; Johnston et al, 2016). In the most optimistic scenario, we can hypothesize that ACE and ACE2 are both genes whose genetic variation and gene expression profiles are at best moderately associated with ME/CFS.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis focused on three case-control GWAS specifically designed to investigate ME/CFS (Herrera et al, 2018; Schlauch et al, 2016; Smith et al, 2011) (Table 1). There were additional genetic association studies using the UK biobank data, as reviewed elsewhere (Dibble et al, 2020). However, these studies contemplated data from individuals who self-reported a clinical diagnosis of ME/CFS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation